HASHTAGS AS MEANING TOOLS GEN Z LANGUAGE ON INSTAGRAM 2025: A STUDY OF SYSTEMIC FUNCTIONAL LINGUISTICS - Novita, Dien; Kusumah, Cita Mustika (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2026)
The study explores the function of hashtags as resources for meaning construction within Generation Z’s Instagram discourse, employing the framework of Systemic Functional Linguistics (SFL). Contrary to prior research that primarily conceptualizes hashtags as technical or organizational devices, this investigation focuses on their linguistic roles in conveying ideational, interpersonal, and textual meanings. Utilizing a qualitative descriptive design and discourse analysis, the study analyzes 120 Instagram captions authored by Gen Z users, encompassing 356 hashtags collected from January to March 2025. An SFL-based coding scheme targeting the three metafunctions guided the data analysis. Results indicate that hashtags contribute substantially across all metafunctions. Ideational meaning predominates (45.5%), with hashtags functioning as condensed representations of experience via experiential labels, circumstantial elements, and abstract notions. Interpersonal meaning constitutes 31.5% of the data, where hashtags articulate stance, affect, and social positioning, frequently through evaluative and emotive expressions. Textual meaning accounts for 23.0%, with hashtags acting as thematic signals, organizers of discourse, and devices linking intertextual elements. Notably, 39.9% of hashtags exhibit multifunctionality by simultaneously fulfilling more than one metafunction. These outcomes underscore that hashtags operate as integral elements within digital discourse, contributing to meaning-making processes that extend beyond conventional clause-based structures. This study broadens the application of SFL by illustrating how non-clausal features like hashtags can effectively perform metafunctional roles in contemporary social media communication. The findings call attention to the importance of incorporating platform-specific features into linguistic analyses to better capture meaning construction in digital environments.